The Influence of the Hello English Application towards Students’ Learning Achievement in Vocabulary Mastery - Astiana, Astiana; Zuhri Dj, Muhammad; Nursidah, Nursidah (Faculty of Education and Teacher Training of IAIN Palopo, 2023)
The objective of this research was to determine the impact of the Hello English application on students' vocabulary acquisition. This study adopted a quasi-experimental design and quantitative research methodology. Data were obtained from 30 eighth-grade students, 15 of whom were in the experimental class and 15 of whom were in the control class. The instrument for data collection was vocabulary tests that were intended to determine if the Hello English program had an effect on students' vocabulary knowledge. The findings of the data analysis indicate that the experimental class's mean score on the pre-test was only 34 but climbed to 57.3 on the post-test. In contrast, the mean pre-test score for the control group was 43, whereas the post-test score was just 39.6. As a result, the class adopting Hello English as the treatment saw a considerable improvement.